Basic mathematics for college students - Benigno, Gloria D. (Manila, Philippines, 2006)
In this new edition, the author has maintained the basic style and approach of this textbook since it has been successfully used by many teachers and students of various Teacher Education Institutions or TEIs. There were some sections which were modified and deleted because they were considered ess important in the development of this book. The Section on Computer Literacy placed at the end of each chapter was deleted since the author believes that Computer Education should be treated fully in another textbook. Most of the exercises in this book are new and word problems were updated. The Check Up Questions after each topic presentation were maintained. Significant portions of the enriched sections were accessed electronically, particularly through the computer program Microsoft Encarta, which provided the biographies of the mathematicians mentioned in this book
Keywords: Mathematics